(3JbfjGJ hCYeGd GdHfhc (B: s (3eMGVQGJ h JeGQjf eMdhdI (B: (3ehLgI dWdHI GdSfI GdKGdKI (BLMD (3, JNUU (B: (3GbJUGO fbOj h Hfcj (B/ s - (3WGgQj GdUOjbs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2019)
(3GdGWGQ GdeaGgjej ddHfhc , GdbQhV GdHfcjI , GdSjGSI GdGFJeGfjI ,GdeNGWQ GdGFJeGfjI h JWHjbGJ h JeGQjf eMdhdI h feGPL GeJMGfGJ (B.s
(3eQGLY U(B.68s
Keywords: (3GdGFJeGfs; (3GdHfhcs; (3GdbQhV GdeUQajIs